Pengaruh Pengawasan dan Budaya Kerja Terhadap Kinerja Karyawan Yang Dimediasi Disiplin Kerja Pada PT. Nilo Engineering Kab. Pelalawan Riau - Lestari, Widya (Jurnal Informatika, 2024)
This research is motivated by the existence of problems seen from the assessment of employee performance at PT Nilo Engineering Kab. Pelalawan Riau which is still lacking in supervision and work culture through work discipline, from the results of the interview the decline occurred because employees could not complete the work according to the specified time. Therefore the authors are interested in conducting research on how the influence of supervision and work culture on performance mediated by work discipline at PT Nilo Engineering in Pelalawan Regency Riau. This research uses quantitative methods. While the population and sample in this study were employees at PT. Nilo Engineering as many as 100 people. The data sources in this study are primary and secondary data. With questionnaire data collection techniques, interviews, and literature studies. To analyze the data used structural equation model analysis with pls by developing a measurement model (outer model) and developing a structural model (inner model). Based on the results of the study, it can be concluded that the research on the Effect of Supervision and Work Culture on Employee Performance mediated by Work Discipline at PT Nilo Engineering Pelalawan Riau, shows that: (1) Work supervision affects work discipline at PT Nilo Engineering Pelalawan Riau. (2) Work culture affects work discipline at PT Nilo Engineering Pelalawan Riau. (3) Work supervision affects employee performance at PT Nilo Engineering Pelalawan Riau. (4) Work culture affects employee performance at PT Nilo Engineering Pelalawan Riau. (5) Work discipline affects employee performance at PT Nilo Engineering Pelalawan Riau. (6) Work supervision affects employee performance with work discipline as a mediating variable at PT Nilo Engineering Pelalawan Riau. (7) Work Culture affects employee performance with work discipline as a mediating variable at PT Nilo Engineering Pelalawan Riau.